DAMPAK MOBILITAS TENAGA KERJA TERHADAP PENDAPATAN RUMAH TANGGA PEDESAAN - HERY SUSILOWATI, SRI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 1 Februari 2005, 2012)
Rural-urban migration activity has increased recently. Those activities resulted both positive and negative impact to rural economy, especially on household income. The purpose of this study is to learn the impact of rural-urban migration on rural household income. The study is based on PATANAS (Panel Petani Nasional) data of 14 West Java villages in 2001. The study concluded that rural-urban migration has a positive impact both on rural household income and rural economic development Total household’s income is significantly influenced by remittance while household’s income comes from migration activity is significantly influenced by level of education and number of migrate household’s members.
Keywords: Impact, Rural-Urban, Migration, Household Income.